Wealth accumulation by hypogamy in own and parental education in China. Issue 2 (6th October 2021) - Cheng, Cheng; Zhou, Yang
Abstract: Objective: This study examines how household wealth accumulation varies by different types of hypogamy on the basis of couples' own and parental education. Background: Educational hypogamy (wives having more education than their husbands) is increasingly relevant in many societies, given the reversal of the gender gap in education. Prior research has studied how marital sorting on couples' own education shapes their individual earnings trajectories. Few have examined the implications of marital sorting on parental education for family‐level economic well‐being. Method: Using data from the 2010–2018 China Family Panel Studies and multilevel growth curve models, this study examined how household wealth trajectories over years of marriage differ by types of hypogamy. Hypogamy in the child generation (wives having more education), hypogamy in the parent generation (wives having more parental education), and hypogamy in both generations (wives having more own and parental education) were compared to hypogamy in neither generation (wives having neither more own nor parental education). Results: Hypogamy in either the child or the parent generation accumulated more total wealth and housing wealth than hypogamy in neither generation. Hypogamy in both generations experienced the fastest gains in total wealth. Conclusion: Hypogamy on the basis of couples' own or parental education is associated with more household wealth and faster wealth accumulation over years of marriage. Implications: This study sheds light on the long‐term implications of hypogamy based on the education of two generations for wealth stratification.